Tracking the resource pulse: Movement responses of fish to dynamic floodplain habitat in a tropical river. Issue 3 (26th December 2019) - Crook, David A.; Buckle, Duncan J.; Morrongiello, John R.; Allsop, Quentin A.; Baldwin, Wayne; Saunders, Thor M.; Douglas, Michael M.
Abstract: Natural river floodplains are among the Earth's most biologically diverse and productive ecosystems but face a range of critical threats due to human disturbance. Understanding the ecological processes that support biodiversity and productivity in floodplain rivers is essential for their future protection and rehabilitation. Fish assemblage structure on tropical river floodplains is widely considered to be driven by dispersal limitation during the wet season and by environmental filtering and interspecific interactions during the dry season. However, the individual‐level movement behaviours (e.g. site attachment, nomadism, homing) that regulate dispersal of fish on floodplains are poorly understood. We combined radiotelemetry and remote sensing to examine the movement behaviour of two large‐bodied fishes (barramundi Lates calcarifer, forktail catfish Neoarius leptaspis ) over the flood cycle in a tropical river‐floodplain system in northern Australia to: (a) quantify movement responses in relation to dynamic habitat resources at a landscape scale; and (b) determine the extent of spatial 'reshuffling' of individual fish following the wet season. Both species altered their behaviour rapidly in response to changes in the availability and distribution of aquatic habitat, with most individuals undertaking extensive movements (up to ~27 km from the tagging location) on the inundated floodplain during the wet season. Although there was considerable individual variation in movement patterns, overall barramundi distributions closely tracked the extent of floodplain primary productivity, whereas catfish distributions were most closely associated with the extent of flooded area. Most individuals of both species exhibited homing back to previously occupied dry season refugia during the wet‐to‐dry transition, even though other potential refugia were available in closer proximity to wet season activity areas. We postulate that homing behaviour modulates temporal variation in fish assemblage composition and abundance and limits the transfer of aquatic‐derived energy and nutrients into terrestrial food webs by reducing fish mortality on drying floodplains. Our study demonstrates the importance of quantifying individual‐level behaviour across the three stages of dispersal (emigration, inter‐patch movement, immigration) for our understanding of how animal movement influences energetic subsidies and other large‐scale ecosystem processes. Abstract : This manuscript describes a landscape‐scale study of the movements of two riverine fish species over a wet season in tropical northern Australia. The study combines radiotelemetry and remote sensing to address key gaps in our understanding of factors that drive species assemblage structure and ecosystem processes in floodplain rivers. Photo credit for the image is Michael Lawrence‐Taylor.